Augmentation of students’ research skills in fieldwork approaches to history, ICSS, Malaysia - Salleh, Mohamad Johdi; Madin, Abu Bakar (2011)
The study discusses the perception of students on the augmentation or development of research skills in fieldwork approaches to history, Integrated Curriculum for Secondary Schools (ICSS), Malaysia. The study was conducted in various types of schools in Perak and Terengganu which involved about eight hundred multi-ethnics students of Forms One, Two, Three, and Four, from Science, Religious, and Regular streams. The instruments used were questionnaire and interview. The data was analysed by using SPSS and presented in percentage, frequency, means, and standard deviation. The result of the study shows a high relation concerning the students’ perceptions of fieldwork approaches to history and the development of research skills among them. The highest perception was that a fieldwork would develop students to ‘make deductions from historical sources’ and ‘suggest reasons why people in the past acted as they did’. It is hoped that more students would benefit from this core subject of the lower and upper secondary levels, ICSS Malaysia, towards the realisation of the twenty-first millennium first class human capital of Malaysian and 1-Malaysia nation.